Impacts of the dry season on the gas exchange of oil palm (iElaeis guineensis/i) and interspecific hybrid (iElaeis oleifera/i x iElaeis guineensis/i) progenies under field conditions in eastern Colombia (2016)
Elaeis guineensis palms and its interspecific hybrid (E. oleifera × E. guineensis) were planted in 2004 in the Cuernavaca farm of Unipalma S.A., located in the municipality of Paratebueno Cundinamarca, Colombia). The palms were planted in two fields: Mecasaragua and Aurora. The first field has never been irrigated, and the second one (Aurora) has always been floodirrigated during the dry season according to the parameters of the plantation. In this study, physiological parameters (gas exchange and water potential) were assessed in three seasons of the year 2013 (dry season, dry-to-wet transition season and wet season). Significant gas exchange differences were found among the seasons in the field with no irrigation (Mecasaragua). Likewise, differences between the genetic materials were observed during the dry season. For example, the hotosynthesis decreased by 75% compared with the palms planted in the irrigated field. No differences among seasons or materials were found in the irrigated field (Aurora). E. guineensis palms were more sensitive to water stress compared with the O×G interspecific hybrid. Both genetic materials responded rapidly to the first rains by leveling their photosynthetic rates and demonstrated an excellent capacity to recover from water stress.